2018
DOI: 10.1002/smll.201702446
|View full text |Cite
|
Sign up to set email alerts
|

Paraptosis‐Inducing Nanomedicine Overcomes Cancer Drug Resistance for a Potent Cancer Therapy

Abstract: Most chemotherapeutic drugs and their nanomedicine formulations exert anticancer activity by inducing cancer cell apoptosis. However, cancer cells inherently have and acquire many antiapoptosis mechanisms, causing cancer drug resistance and poor prognoses in patients. Herein, a potent paraptosis‐inducing nanomedicine is reported that causes quick nonapoptotic death of cancer cells, overcoming apoptosis‐based resistance and effectively inhibiting drug‐resistant tumor growth. The nanomedicine is composed of mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 52 publications
2
51
0
Order By: Relevance
“…Mitogen‐activated protein kinases (MAPKs), including c‐Jun N‐terminal kinases (JNKs) have been implicated . The initiation of paraptosis by many drugs is associated with a misfolded protein response involving the ER . It appears that paraptosis can be a pathway to eradication of cells with an impaired apoptotic program .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitogen‐activated protein kinases (MAPKs), including c‐Jun N‐terminal kinases (JNKs) have been implicated . The initiation of paraptosis by many drugs is associated with a misfolded protein response involving the ER . It appears that paraptosis can be a pathway to eradication of cells with an impaired apoptotic program .…”
Section: Introductionmentioning
confidence: 99%
“…The initiation of paraptosis by many drugs is associated with a misfolded protein response involving the ER . It appears that paraptosis can be a pathway to eradication of cells with an impaired apoptotic program . Studies reported here were designed to further characterize the elements of paraptosis in OVCAR‐5 cells.…”
Section: Introductionmentioning
confidence: 99%
“…[94,141] However, clinical use of copper-based cytotoxins is still limited due to their very low water-solubility and instability in in vivo transportation. An important character of some copper-based cytotoxins, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…[135] Adv. [141] Most chemotherapeutics and their nanoformulations kill cancer cells by inducing caspase-dependent apoptosis. 2019, 2 In addition, Greish et al reported that curcumin-copper complex encapsulated in poly(styrene-co-maleic acid) micelles could abolish the growth of triple-negative breast cancer in vivo without overt side effects.…”
Section: Copper Nanotoxinsmentioning
confidence: 99%
See 1 more Smart Citation